Eradicating Child Labor in Kosovo: The Strategic Role of ILO through the MAP16 Initiative - Ridwan, Bintang Syaharani; Gonda Yumitro (Department of International Relations, Brawijaya University, 2025)
The issue of child labor remains a serious challenge in Kosovo, requiring the intervention of international actors such as the International Labor Organization (ILO). This study aims to analyze the role of the ILO in accelerating the elimination of child labor through the Measurement, Awareness Raising, and Policy Engagement (MAP16) project. Using qualitative descriptive analysis methods, this research examines the ILO's role as an instrument providing technical and financial assistance, as an arena for stakeholder collaboration, and as an actor actively engaged in advocacy and public campaigns. The findings indicate that the ILO's involvement through MAP16 strengthens cross-sectoral coordination and the effectiveness of implementing ILO Conventions No. 182 and No. 138. These findings highlight the crucial role of international institutions in driving sustainable policy and practice changes in efforts to eliminate child labor.